Diagnostic Test of Urine Proteome during Atherosclerotic Process Among White Rat (Rattus Novergicus Strain Wistar) Induced by Atherogenic Diet - Rosita, Linda; Devita, Ninda (Bangladesh Journal of Medical Science, 2016)
Introduction: Around twenty five million people in United State have at least one complications of atherosclerosis such as cardiovascular disease. Therefore screening in atherosclerotic process is important. Atherosclerosis is a multistage process that begins with damage to the endothelium due to LDL exposure. Angiography Coronary is the primary diagnostic tool for atherosclerosis. Imaging, as one way of non-invasive diagnosis, have limitation in sensitivity, specificity, and cost. Proteome urine analysis is alternative for atherosclerosis diagnostic. Objective: The aim of this study was analyse diagnostic performance of urine proteome among white rat (Rattus Novergicus strain wistar) induced by atherogenic diet. Material and methods: This study was quasi experimental in laboratory with randomized posttest only for control group design. The rat samples were divided to two groups i.e. group with atherogenic diet and non-atherogenic diet. Each group consisted of 10 rats. The treatment was done for 15 weeks. Urine sample collection was performed in week 16 of treatment. Urine proteome, collagen type I, was analyzed by ELISA to obtain biomarkers of atherosclerosis. Then determined sensitivity and specificity of the proteome urine analysis was compared with histopathology findings of the aortic arch and its branches. Result: In week 16, the researchers collected sample from 16 rats i.e. 11 rats with atherogenic diet and 5 ratswith non-atherogenic diet. Urine proteome, collagen type I, had area under the receiver operator with the characteristic curve of 98.2% (95% IK 92.6%-100%), p 0,003. The bestcut offis 0.9025 ng/ml with sensitivity of 100% and specificity of 90.9%. Conclusion: Urine proteome analyse, collagen type I, had high accuracy for atherosclerosis diagnostic. Bangladesh Journal of Medical Science Vol.15(4) 2016 p.522-528